2015
DOI: 10.1007/s00705-015-2717-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of beak and feather disease virus prevalence and immunity-associated genetic diversity over time in an island population of red-crowned parakeets

Abstract: Pathogen outbreaks in the wild can contribute to a population's extinction risk. Concern over the effects of pathogen outbreaks in wildlife is amplified in small, threatened populations, where degradation of genetic diversity may hinder natural selection for enhanced immunocompetence. Beak and feather disease virus (BFDV) was detected for the first time in an island population of red-crowned parakeets (Cyanoramphus novaezelandiae) in 2008 on Little Barrier Island (Hauturu-o-Toi) of New Zealand. By 2013, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…However, studies on the cause–response relationships between TLRs and viral pathogens in wildlife remain rare. Knafler et al ( 2016 ) have shown a relationship between TLR3 and the beak and feather virus in red-crowned parakeets ( Cyanoramphus novaezelandiae ), but without further elaborating on the effect of specific haplotypes on infection status. Loots et al ( 2018 ) reported a possible beneficial effect of a SNP in TLR2 on canine distemper virus susceptibility in South African lions, resulting in an amino acid exchange within the LRR.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the cause–response relationships between TLRs and viral pathogens in wildlife remain rare. Knafler et al ( 2016 ) have shown a relationship between TLR3 and the beak and feather virus in red-crowned parakeets ( Cyanoramphus novaezelandiae ), but without further elaborating on the effect of specific haplotypes on infection status. Loots et al ( 2018 ) reported a possible beneficial effect of a SNP in TLR2 on canine distemper virus susceptibility in South African lions, resulting in an amino acid exchange within the LRR.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity and population structure of the RSSC strains prevalent in Malagasy potato growing basins were investigated, and our understanding of potato BW epidemiology was improved. Most studies have investigated the population diversity and biology of plant pathogens to gain better insight into disease etiology ( Milgroom and Peever, 2003 ). Major agronomic areas of the potato growing basins of Madagascar were prospected for RSSC strains at different agroecological scales and strains were typed using MLVA schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there has been little to no genetic exchange between the populations for decades, these differences can most likely be attributed to genetic drift. Previous research in other bird species has also found genetic differentiation in both neutral (microsatellites) and TLR loci, which generally indicates that genetic drift may be stronger than selection (Gonzalez-Quevedo et al, 2015;Grueber et al, 2013;Knafler et al, 2016). However, it is possible that selection at TLR loci may contribute to the genetic differentiation between populations (Grueber et al, 2013;Knafler et al, 2016Knafler et al, , 2017.…”
Section: Discussionmentioning
confidence: 91%